2018
DOI: 10.1038/s41598-018-24471-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Three Different Mutations in Ehrlichia chaffeensis in Altering the Global Gene Expression Patterns

Abstract: The rickettsial pathogen Ehrlichia chaffeensis causes a tick-borne disease, human monocytic ehrlichiosis. Mutations within certain genomic locations of the pathogen aid in understanding the pathogenesis and in developing attenuated vaccines. Our previous studies demonstrated that mutations in different genomic sites in E. chaffeensis caused variable impacts on their growth and attenuation in vertebrate and tick hosts. Here, we assessed the effect of three mutations on transcriptional changes using RNA deep-seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 63 publications
5
19
0
1
Order By: Relevance
“…We previously reported 9 random mutations within the E. chaffeensis genome in our prior study ( 14 ). Subsequent research has focused on detailed characterization of three mutant E. chaffeensis organisms ( 16 , 17 , 36 , 37 ). These studies aided in the identification of one mutation in the ECH_0660 gene causing the rapid clearance of the pathogen and inducing a sufficient host immune response to serve as a live attenuated vaccine to protect against wild-type infection challenge by intravenous (i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported 9 random mutations within the E. chaffeensis genome in our prior study ( 14 ). Subsequent research has focused on detailed characterization of three mutant E. chaffeensis organisms ( 16 , 17 , 36 , 37 ). These studies aided in the identification of one mutation in the ECH_0660 gene causing the rapid clearance of the pathogen and inducing a sufficient host immune response to serve as a live attenuated vaccine to protect against wild-type infection challenge by intravenous (i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, también existen otras opciones como son las células Vero (células de riñón de mono verde) y HL60 (células de leucemia promielocítica humana). No obstante, el cultivo de éstas resulta ser un proceso difícil y que requiere de experiencia 34,35 . Por otra parte, se ha reportado el aislamiento de E. canis en líneas celulares de garrapatas.…”
Section: Wwwrevinfclunclassified
“…While a mutation downstream to the ECH_0490 gene caused enhanced transcription from stress response genes, which possibly helped the mutant to better survive in vertebrate hosts. Mutation within the ECH_0660 gene, encoding for a phage like protein, showed minimal transcriptional variations compared to the wildtype strain, thus keeping the integrity of its transcriptome similar to wildtype E. chaffeensis (Kondethimmanahalli and Ganta, 2018 ). While we predict that the transcriptome data are suggestive of protein expression variations, additional experimental validation at the protein level is needed to confirm the results.…”
Section: Introductionmentioning
confidence: 97%
“…Further, gene function disruption mutations within the genes ECH_0379 and ECH_0660 offered partial and complete protection against infection in a vertebrate host, respectively, while mutation in ECH_0230 offered no protection (Cheng et al, 2013 , 2015 ; Nair et al, 2015 ; McGill et al, 2018 ). Our recent RNA deep sequencing study reported that mutation in ECH_0379 gene that codes for an anti-porter protein caused drastic down-regulation of several genes (Kondethimmanahalli and Ganta, 2018 ). While a mutation downstream to the ECH_0490 gene caused enhanced transcription from stress response genes, which possibly helped the mutant to better survive in vertebrate hosts.…”
Section: Introductionmentioning
confidence: 99%